Spondylodiscitida, epidurální empyém jako komplikace syndromu diabetické nohy - Cechurová, D; Lacigová, S; Zourek, M; Gruberová, J; Haladová, I; Tomešová, J; Rušavý, Z (Vnitrni lekarstvi, 2013)
UNLABELLED: Spinal column infection (vertebral osteomyelitis, discitis, epidural empyema/ abscess) is a rare condition, albeit its incidence has been increasing in recent years. Staphylococcus aureus is the most frequent pathogen. The routes of infection are predominantly hematogenous. Any delay in making correct diagnosis increases risk of adverse outcome of the patient. The authors present 3 case reports of patients with diabetic foot syndrome, who were diagnosed with spondylodicitis in the period of 2009- 2012, two patients had associated epidural empyema. Apart of a chronic neuropathic foot wound, the patients reported severe or deteriorated dorsal pain (2 in the lumbal region, one in thoracic spine), had no new neurologic lesion in the beginning, some had fever, but all had high laboratory parameters of inflammation that did not correlate with local finding on the foot. Methicillin sensitive Staphylococcus aureus cultured from the foot defect in all cases, in two patients from blood cultures and from epidural empyema. They were patients with recurrent local infectious complications of diabetic foot ulcers. Two patients had a concomitant diabetic nephropathy, classified into stages 3- 4/ 5 according to K/ DOQI. Glycemic control (Type 1, Type 2 and secondary DM) ranged from excellent to unsatisfactory (HbA1c 43- 100 mmol/ mol). Apart of patient history and clinical examination, the magnetic resonance imaging of the spine was essential for the diagnosis of spondylodiscitis, or epidural empyema. The treatment was founded on longterm (initially parenteral) antibiotic treatment, bed rest, then mobilization with orthosis. Neurosurgical procedure was necessary in the patients with epidural empyema. All patients were mobile following a varied time period of convalescence and rehabilitation. CONCLUSION: Dorsal pain and degenerative changes of the spinal column belong to common findings in our population. When searching for the origin of an infection in patients with elevated inflammatory parameters (inadequate finding for a diabetic ulcer), the history of dorsal pain suddenly becomes the fundamental clue for diagnosis of spondylodiscitis with or without epidural empyema.
Keywords: Discitis; lidé středního věku; epidurální absces; Adult; Male; Aged; dospělí; lidé; mužské pohlaví; senioři; Diabetic Foot; discitida; Epidural Abscess; Humans; Middle Aged; diabetická noha